Antibacterial effect of water-soluble chitosan on representative dental pathogens Streptococcus mutans and Lactobacilli brevis (Journal of Applied Oral Science, 2012)
Dental caries is still a major oral health problem in most industrialized countries. The development of dental caries primarily involves Lactobacilli spp. and Streptococcus mutans. Although antibacterial ingredients are used against oral bacteria to reduce dental caries, some reports that show partial antibacterial ingredients could result in side effects. OBJECTIVES: The main objective is to test the antibacterial effect of water-soluble chitosan while the evaluation of the mouthwash appears as a secondary aim. MATERIAL AND METHODS: The chitosan was obtained from the Application Chemistry Company (Taiwan). The authors investigated the antibacterial effects of water-soluble chitosan against oral bacteria at different temperatures (25-37ºC) and pH values (pH 5-8), and evaluated the antibacterial activities of a self-made water-soluble chitosan-containing mouthwash by in vitro and in vivo experiments, and analyzed the acute toxicity of the mouthwashes. The acute toxicity was analyzed with the pollen tube growth (PTG) test. The growth inhibition values against the logarithmic scale of the test concentrations produced a concentrationresponse curve. The IC50 value was calculated by interpolation from the data. RESULTS: The effect of the pH variation (5-8) on the antibacterial activity of water-soluble chitosan against tested oral bacteria was not significant. The maximal antibacterial activity of water-soluble chitosan occurred at 37ºC. The minimum bactericidal concentration (MBC) of water-soluble chitosan on Streptococcus mutans and Lactobacilli brevis were 400 µg/mL and 500 µg/mL, respectively. Only 5 s of contact between water-soluble chitosan and oral bacteria attained at least 99.60% antibacterial activity at a concentration of 500 µg/mL. The water-soluble chitosan-containing mouthwash significantly demonstrated antibacterial activity that was similar to that of commercial mouthwashes (>;99.91%) in both in vitro and in vivo experiments. In addition, the alcohol-free mouthwash exhibited no cytotoxicity and no oral stinging. To the best of our knowledge, this was the first study to combine in vitro and in vivo investigations to analyze the antibacterial properties of water-soluble chitosan-containing mouthwash. CONCLUSIONS: This study illustrated that water-soluble chitosan may be a viable alternative to commercial mouthwashes in the future.